2016
DOI: 10.1902/jop.2016.150539
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Rhinitis Is Associated With Periodontitis: A Population‐Based Study

Abstract: An association between periodontitis and prior AR is demonstrated. It is recommended that physicians be more alert for potential risk of subsequent development of CP in patients with AR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 43 publications
1
17
2
Order By: Relevance
“…Thus, such a high fidelity of coding system in the NHIRD would be expected to provide authentic statistical representation of data for analyzing epidemiological profiles of the entire Taiwanese population. Supporting its validity, several high‐quality studies have been published based on the LHID2005 …”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, such a high fidelity of coding system in the NHIRD would be expected to provide authentic statistical representation of data for analyzing epidemiological profiles of the entire Taiwanese population. Supporting its validity, several high‐quality studies have been published based on the LHID2005 …”
Section: Methodsmentioning
confidence: 97%
“…The retrospective analysis in this cohort study was conducted using two study groups: a newly onset periodontitis group and a matched non‐periodontitis (comparison) group, both recruited in the period 2002‐2008. Patients aged 40 or more with at least two outpatient service claims under the diagnosis codes of periodontitis (ICD‐9‐CM code 5234) were identified as the periodontitis cohort . Individuals meeting the inclusion criteria were further categorized into one of three periodontitis subtypes .…”
Section: Methodsmentioning
confidence: 99%
“…Studies on the association of AR with caries and periodontitis are few, and they show conflicting results (Wongkamhaeng et al 2014; Hung SH et al 2016;Bakhshaee et al 2017;Kim et al 2018). The association between AS and pulpitis and stomatitis; and between AR and pulpitis, gingivitis, and stomatitis have scarcely been studied.…”
Section: Introductionmentioning
confidence: 99%
“…No studies have been reported in adults. The relationship between AR and periodontitis is inconclusive, because both positive(Hung SH et al 2016) and inverse(Kim et al 2018) associations have been reported. To the best of our knowledge, an association between AR and gingivitis, pulpitis, and stomatitis/aphthae has not been reported previously.…”
mentioning
confidence: 99%
“…I have carefully read the article on the association between allergic rhinitis (AR) and chronic periodontitis (CP) 1 . Congratulations to the authors for conducting a unique study.…”
mentioning
confidence: 99%